The poetry of Cao Zhi - Cao, Zhi 192-232 (De Gruyter, 2021)
This volume provides a translation of the complete poems and fu of the early medieval poet Cao Zhi (192-232), one of the most celebrated figures in Chinese literary history. The translation is based on a valuable critical edition of Cao's works by Ding Yan (1794-1875). In addition to the translation, the present work also offers robust textual notes of its own, a brief biography of Cao Zhi, and an introduction to his poetry--back cover
Erscheint als Open Access bei De Gruyter
Keywords: Cao, Zhi -- 192-232; Lyrik; Englisch; Übersetzung; Hardback; Fachpublikum/ Wissenschaft; LIT008000; Cao Zhi; Chinese Poetry; Early Medieval; Jian'an; PN: nicht rabattbeschränkt/Sortimentstitel; 1560: Hardcover, Softcover / Sprachwissenschaft, Literaturwissenschaft; Anthologie